Izbrane naravnogeografske značilnosti občine Radlje ob Dravi - Žiberna, Igor (Revija za geografijo, 2011)
The article treats relations between land use and selected physical geographical charactersitics of Radlje ob Dravi municipality. Methodology of gathering data and statistical analysis is presented. Within geographical information system methodology the frequency of land use categories and their connection with physical geographical characteristics are analysed.
Keywords: fizična geografija; geografski informacijski sistemi; geographical information system; Kozjak; land use; physical geography; Pohorje; raba tal; Radlje ob Dravi